PAYMENT SYSTEM INSTALLMENT LOANS, AND COOPERATIVE EMPLOYEES AT JARAHNITRA USING MICROSOFT VISUAL BASIC 6.0 - Dira Suprima; Cut Asiana Gemawaty, SKom, MMSi (Jurnal Sistem Informasi, 2004)
Along with the rapid development era, the increasingly complex problems faced byhumans. The necessity to solve a problem quickly, precisely and efficiently areurgently needed. Therefore, information science and technology is always developedto make it happen.The role of the computer provides an enormous impact on human life, as evidence ofalmost all types of businesses use computers as a tool to speed up data processing.Among the economic sector in the process of granting credit or installment loans andcalculations that must be paid to the cooperative.In this study, the authors make a computerized system for credit granting process inthe form of loans or credit goods that accompanied the installment payments onCooperative Jarahnitra using Microsoft Visual Basic 6.0 to help accelerate theprocess of data processing.